PEDAGOGICAL CONTENT KNOWLEDGE PROFILE OF PROSPECTIVE CHEMISTRY TEACHER - Tonih Feronika (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
PROFIL PEDAGOGICAL CONTENT KNOWLEDGE CALON GURU KIMIAAbstractIn 2013 Dilek Karışan and Ayşe Şenay conducted experiments to investigate the Pedagogical Content Knowledge (PCK) of science teachers from Turkey that resulted in good teacher involvement determining the optimal formation of Content Knowledge in curriculum achievement, knowledge improvement and students are ready to learn. Chemical Education Study Program of UIN Syarif Hidayatullah Jakarta, Chemistry teacher who must have pedagogic and professional competence, to get concrete information from student's competence as the basis for developing KKNI curriculum of Chemistry Education Study Program. Therefore, the researcher will describe Pedagogical Content Knowledge Profile of pree-service Chemistry Teacher. Through qualitative descriptive method Mastery of PCK understanding by analyzing the answer of test result using Certainty of Response Index Criteria (CRI). Result of research PCK prospective teacher of chemistry is to know concept (49,7%) and misconceptions (50.3%). Based on the concept of chemistry of prospective teachers is to know the concept (40.4%) and do not know the concept (59.6%). This result is a consideration of the Institute for Educational Teaching Program (LPTK), especially the Chemistry Education Study Program as the basis for developing the KKNI Curriculum in the preparation of Learning Outcome Study and Leson Plan of Study. AbstrakPada tahun 2013 Dilek Karışan dan Ayşe Şenay melakukan eksperimen mengivestigasi Pedagogical Content Knowledge (PCK) guru sains dari di Turki dihasilkan bahwa kertelibatan guru secara baik menentukan pembentukan Content Knowledge secara optimum dalam pencapaian kurikulum, peningkatan pengetahuan dan siswa siap untuk belajar. Program Studi Pendidikan Kimia UIN Syarif Hidayatullah Jakarta mencetak calon Guru kimia yang harus memiliki kompetensi pedagogik dan professional,untuk mendapatkan informasi kongkrit dari kompetensi mahasiswa sebagai dasar untuk mengembangkan kurikulum KKNI Program Studi Pendidikan Kimia. Maka dengan ini peneliti akan mendeskripsikan Profil Pedagogical Content Knowledge Calon Guru Kimia.. Melalui metode deskriptif kualitatif Penguasaan pemahaman PCK dengan menganalisis Jawaban hasil tes menggunakan Kriteria Certainty of Response Index (CRI), Hasil penelitian Profil PCK calon guru kimia adalah tahu konsep (49,7%) dan miskonsepsi (50,3%). Berdasarkan pengusaan konsep kimia calon guru adalah tahu konsep (40,4%) dan tidak tahu konsep (59,6%). Hasil ini menjadi pertimbangan terhadap Lembaga Pendidikan Tenaga Kependidikan (LPTK) khususnya Program Studi Pendidikan Kimia sebagai dasar dalam mengembangkan Kurikulum KKNI dalam penyusunan Learning Outcome Program studi dan Rencana Perkuliah Semester.